Comment et l’expression de la quantité en français québécois de tous les jours. Je me demande comment ça coûte, comment il y a de neige, ça fait comment de temps - Gaétane Dostie (Studii de Lingvistica)
This article investigates the quantitative use of COMMENT ‘how’ (comment-Q ‘how much’) in Quebec French, used in a sentence such as j’ai hâte de voir comment ça va coûter ‘I can’t wait to see how much it will cost’. In this type of context, comment-Q commutes with the quantitative COMBIEN (combien-Q ‘how much’). The study is based on data taken from the Corpus de français parlé au Québec (CFPQ), a database of casual conversations recorded on audiovisual support between 2006 and 2019 in various regions of Quebec. The study has four objectives. The aim is 1) to determine the frequency of comment-Q within the set of meanings expressed by the marker COMMENT in synchrony, 2) to determine whether comment-Q and combien-Q are exact synonyms, 3) to identify the factors likely to have concurred in the emergence of comment-Q in the variety of French being studied, 4) to position comment-Q in relation to other meanings expressed by COMMENT, in particular those referring to intensity and manner.